2022
DOI: 10.1111/bph.15655
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA methylation de‐represses peroxisome proliferator‐activated receptor‐γ and attenuates pulmonary fibrosis

Abstract: Background and Purpose: Development of pulmonary fibrosis is associated with altered DNA methylation modifications of fibrogenic gene expression. However, their causal relationships and the underlying mechanisms remain unclear. This study investigates the critical role of DNA methylation aberration-associated suppression of peroxisome proliferator-activated receptor-γ (PPARγ) in pulmonary fibrosis. Experimental Approach: Expression of PPARγ and bioactive DNA methyltransferases (DNMTs) and PPARγ promoter methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The Fbxw7 promoter can be regulated through epigenetic mechanism during lung fibrosis, including histone modifications. Aberrant elevation of DNA methyltransferase 1 (Dnmt1) can mediate the hypermethylation of Fbxw7 promoter and result in decreased gene level of Fbxw7 ( 65 ), subsequently contributes significantly to the development of pulmonary fibrosis ( 66 ). Moreover, the expression of enhancer of zeste homolog 2 (Ezh2) is increased in IPF patients, increased Ezh2 recruitment and hypermethylated H3K27 at the promoter of fibrotic related genes have been demonstrated, such as Cox-2 ( 67 ) and Cxcl10 ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Fbxw7 promoter can be regulated through epigenetic mechanism during lung fibrosis, including histone modifications. Aberrant elevation of DNA methyltransferase 1 (Dnmt1) can mediate the hypermethylation of Fbxw7 promoter and result in decreased gene level of Fbxw7 ( 65 ), subsequently contributes significantly to the development of pulmonary fibrosis ( 66 ). Moreover, the expression of enhancer of zeste homolog 2 (Ezh2) is increased in IPF patients, increased Ezh2 recruitment and hypermethylated H3K27 at the promoter of fibrotic related genes have been demonstrated, such as Cox-2 ( 67 ) and Cxcl10 ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together with DNMT3B, DNMT3A also catalyzes de novo DNA methylation, while the DNMT1 maintains DNA methylation [ 16 ]. Therefore, we cannot rule out a potential role of DNMT3A and DNMT1 in regulating macrophage polarization during fibrosis, and other studies have already shown that both DNMT1 and DNMT3A play a role in the development of pulmonary fibrosis by modulating DNA methylation in lung fibroblasts and alveolar epithelial cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DNMT3A-induced silencing of SOCS3 expression stimulates TGF-β-dependent fibroblast activation in experimental systemic sclerosis (SSc) murine models [ 70 ]. A recent study found that the peroxisome proliferator-activated receptor-γ (PPARγ) expression was low, but increased DNMT 1/DNMT3a and PPARγ promoter hypermethylation in IPF patients; therefore, the inhibition of DNA methylation that restored PPARγ led to attenuated pulmonary fibrosis [ 71 ]. The aberrant expression of DNMTs patterns is associated with pulmonary fibrosis, although the exact mechanisms underlying this pathogenesis remain elusive.…”
Section: Epigeneticsmentioning
confidence: 99%
“…In addition, 5aza reduced global DNA methylation in chemo-sensitive cancer cells [ 143 ]. Targeting DNMT 1/DNMT3a and the peroxisome proliferator-activated receptor-γ (PPAR-γ) axis with 5-aza can demethylate the PPAR-γ promoter, restore PPAR-γ loss, and alleviate fibrotic lung [ 71 ].…”
Section: Targeted Gene and Personalized Medicinementioning
confidence: 99%